Is Personality the Key Factor in Becoming a SuperAger? - Ritika Batra; Deepa Anil Kumar; Gauri Shanker Kaloiya; Maroof Ahmad Khan; Sujata Satapathy; Avinash Chakrawarty; Ashish Datt Upadhyay; Prasun Chatterjee (Journal of the Indian Academy of Geriatrics)
Background: This study investigates the personality of SuperAgers (SAs). Fifty-five older adults were assessed using Rey auditory verbal learning test (RAVLT), Wechsler adult intelligence scale- Fourth Edition India (WAIS IV), Color trails test (CTT), and Boston naming test (BNT) and categorized as SAs or typical older adults (TOAs). Their personality profiles were compared using NEO-PI-3, alongside 50 participants aged 25–50 years. Materials and Methods: The study analyzed 105 participants. Informed consent was obtained from all individuals. Personality traits were evaluated using NEO-PI-3 across three groups. The Geriatric Depression Scale-30 (GDS-30) was used to assess depression. Results: SA excelled in all personality domains compared to TOA. Significant differences were noted in neuroticism (SA = 49.08 ± 6.93; TOA = 52.03 ± 7.24) and agreeableness (SA = 45.95 ± 8.82; TOA = 41.90 ± 8.33) (P < 0.001). GDS-30 scores revealed SA as normal (1.96 ± 2.82), while TOA scored in mild range (11.58 ± 3.30) (P < 0.001). Conclusion: The study highlights SAs’ superior performance across personality domains and lower depressive symptoms compared to TOA. These findings highlight key distinctions, demonstrating cognitive resilience in aging.